Landscapes of (re)conquest: dynamics of multicultural frontiers in medieval South-west Europe. (June 2020) - García-Contreras, Guillermo; Pluskowski, Aleks; Alexander, Michelle; Banerjea, Rowena; García, Marcos García
Abstract: Abstract : The 'Landscapes of (Re)Conquest' project investigates the dynamics of medieval frontier societies in South-west Europe through the lens of the cultural landscape. It compares diverse regional borderlands in Spain, created by successive waves of Islamic and Christian conquests, with the Pyrenean frontier on either side of the Albigensian Crusade and aims to reconnect the castles of frontier authorities with their associated territories from a heritage perspective.